The relationship between OSHA practices towards job satisfaction at Azhar Food Supplier Sdn. Bhd. / Nurul Ameera Salehan - Salehan, Nurul Ameera (Faculty of Business and Management, 2019)
This study is to examine the significant relationship between Occupational Safety and Health (OSHA) practices on job satisfaction at Azhar Food Supplier Sdn. Bhd. In addition it also wants to examine the most influent occupational safety and health practice on job satisfaction at the organization. The method used to collect the data is by using questionnaire and through probability sampling which is simple random sampling. 73 out of 90 respondent had answer the survey. Between the three variables, in recovery of the study it is discovered that all factor have huge connection between job satisfaction. This answers had resulted that all of three of the hypothesis is significant and accepted.